A CASE OF MULTIORGAN DYSFUNCTION DUE TO SCRUB TYPHUS INFECTION - A, JEYASURIYA; AK, BADRINATH; R, RAGHUNATHAN (International Journal of Clinical and Biomedical Research, 2016)
Rickettsia tsutsugamushi causes an acute febrile illness known as scrub thypus. Humans get infected when they accidentally encroach the mite infested areas (mite islands) mainly in rural and sub-urban areas1. Scrub typhus is being increasingly reported in India. It should be considered in the differential diagnosis of patients with acute febrile illness, including those with thrombocytopenia, abnormalities in liver function tests, altered sensorium, atypical pneumonia, acute respiratory distress syndrome. We report a case Multi Organ Dysfunction due to scrub typhus infection. A thorough knowledge of scrub typhus including varied presentations and its complications is important for providing life saving treatment for patients.